(Table 1) Isotopes on interstitial gases at DSDP Leg 64 Holes - Martin Schoell (PANGAEA, 1982)
The origin of the interstitial gases of Hole 479 is bacterial. This is indicated by a positive correlation of the 13C concentration in interstitial methane and CO2 in the shallower depths of the hole. Below a depth of 100 meters, the interstitial CO2 becomes increasingly depleted in carbon-13, which indicates a higher rate of CO2-producing decarboxylation reactions rather than a consumption of CO2 for methane production. Alternatively, dolomite formation could account for an increasing depletion of the interstitial CO2. The interstitial gases in Holes 481 and 481A strongly reflect the thermal influence of the dolerite sill. Above the sill, carbon-13 values of -52% and C2/C1 ratios of 10**-2 indicate thermogenically formed hydrocarbon gases. Below the sill, less thermogenic gas formation suggests that convective, rather than conductive, heat transport operated after the sill intruded the wet sediments.
Supplement to: Schoell, M (1982): Stable isotopic analyses of interstitial gases in Quaternary sediments from the Gulf of California. In: Curray, JR; Moore, DG; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 64, 815-817, https://doi.org/10.2973/dsdp.proc.64.126.1982